Research on the Development of Venture Capital and Private Equity Industry in Taiwan - Huang, Chih-Ying (2009)
After 25 year development, VC industry in Taiwan is currently during the transition from early stage VC focusing on financing high-tech industry to later stage PE offering managerial/value-added services for enterprises. However, the development of early stage VC and later stage PE are tremendously different in Taiwan. VC industry has been fully supported and strategically developed by the government policies while PE market is still in its infancy in terms of M&A, buyouts/ins and corporate restructuring. Although the government realizes the importance of domestic VC to transfer to PE, currently there is no complete regulation to help grow PE industry or train PE experts in Taiwan. In addition, the capability of local VC transferring to late stage PE is also a concern because most local VC funds are small-sized and lack of management expertise.